Relating pore hydrophilicity with vapour adsorption capacity in a series of amino acid based metal organic frameworks - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (CrystEngComm, 2013)
A new Zn based porous homochiral metal-organic framework, ThrZnOAc, belonging to unh topology, has been synthesized using pyridyl functionalized threonine and Zn(OAc)(2) as the metal precursor. Stepwise substitution of the homochiral MOF backbone by simply changing the sidearm of the amino acids (isopropyl in the case of valine, methyl in alanine and hydroxyethyl in threonine) resulted in increased water adsorption in ThrZnOAc compared to the previously reported ValZnOAc/AlaZnOAc. Extensive solvent sorption isotherms (water, methanol, isopropanol and toluene) have been carried out, which revealed high solvophilic interaction with polar solvents in ThrZnOAc due to the polar pore [2-hydroxyethyl {-CH(OH)CH3} sidearm of the amino acid], which is not prominent in the corresponding valine/alanine counterparts. The aforementioned functionalization in a series of isostructural amino acid based MOFs with the only difference being in the sidearm and their emergence as enhanced solvophilic materials is unprecedented in the MOF literature.